Assessment of Roadside Drainage Capacity on Lamachaur Road - Kafle, Aayush; Kaphle, Biswash; Pokhrel, Madan (Journal of Engineering and Sciences, 2025)
Lamachaur Road, located in a region prone to heavy rainfall and flash floods during the monsoon season, faces recurring waterlogging and roadway obstructions. In response to these challenges, this study examines the efficiency of existing roadside drainage systems in managing runoff and proposes mitigation strategies. The primary objectives included determining peak runoff during rainfall events, assessing the current drainage capacity, and exploring feasible measures to enhance drainage efficiency. Utilizing the Hydrologic Engineering Center’s River Analysis System (HEC-RAS) software, a hydrological model was developed to simulate runoff dynamics along the Lamachaur Road. Through rigorous analysis, it was revealed that the existing drainage infrastructure operates at a capacity significantly below the required discharge, with an observed deficiency of 82.7%. Quantitatively, the drainage system had a capacity of approximately 4.5 cumecs, insufficient to manage peak runoff volumes during intense precipitation events adequately. Furthermore, attempts to augment drainage capacity by enlarging the size yielded inconclusive results, as the anticipated reduction in flooding was insignificant. Moreover, the prospect of constructing larger drainage systems was constrained by limited roadway space. In conclusion, this study underscores the pressing need for proactive measures to address the inadequacies of roadside drainage infrastructure along Lamachaur Road. By embracing innovative strategies and integrating sustainable water management approaches, sustainable solutions can be realized, enhancing resilience against the challenges posed by monsoon-induced flash floods.